Eleventh Annual Report of Stockholder Activities at Corporation Meetings (Book). - Vance, Lawrence L.; Cannon, Arthur M. (The Accounting Review, 1952)
Reviews the book "Eleventh Annual Report of Stockholder Activities at Corporation Meetings," by Lewis D. Gilbert and John J. Gilbert.